The Penerapan Model Pembelajaran Reciprocal Teaching Untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas V SD Muhammadiyah Perumnas Kota Makassar - Jumiarsi; Pagarra, Hamzah; Rahman, Hardianto (ETEDU : Elementary of Teacher Education, 2025)
This study was motivated by students' low reading comprehension skills in Indonesian language subjects in fifth grade at the Muhammadiyah Perumnas Elementary School in Makassar City. The problem formulation is as follows: How can the application of the reciprocal teaching learning model improve students' reading comprehension skills in Indonesian language subjects in Class V of SD Muhammadiyah Perumnas Makassar City? The aim of this research is to improve the reading comprehension skills of fifth grade students at SD Muhammadiyah Perumnas in Makassar City using the Reciprocal Teaching learning model. The qualitative approach used in this study is the classroom action research (CAR) model of Kemmis and McTaggart. The subjects of the study were 17 fifth-grade students at SD Muhammadiyah Perumnas in the 2024-2025 school year. Data collection techniques included observation, testing, and documentation, and data analysis employed quantitative and qualitative methods. The results showed an increase in students' reading comprehension skills in Indonesian language subjects from cycle I to cycle II. Pre-cycle data showed that no students reached the completeness standard. Cycle I showed an increase, though both meetings were still in the very low category. Furthermore, Cycle II implementation showed a significant increase in the first meeting.